GAMIFIKASI DALAM PEMBELAJARAN MATEMATIKA MELALUI PRODUCTIVE STRUGGLE SEBAGAI SOLUSI PEMBELAJARAN SELAMA PANDEMI - Muhammad Rijal Wahid Muharram; Widani Widani (IKIP Siliwangi, 2021)
This study aims to know the design of mathematics learning using the principle of gamification through productive struggle as a learning solution during the pandemic. This study used a descriptive qualitative approach with secondary data from several theories. The data collection process is carried out through a literature study that known as library research. The result of this study is an analysis of the application of gamification in mathematics learning through productive struggle design based on the characteristics of gamification and productive struggle concept. So, it can be concluded that the design of gamification through productive struggle in mathematics learning consist of these steps: 1) Teachers and students have an agreement for implementing gamification in mathematics learning; 2) The teacher introduces the challenges to students that must be faced and resolved; 3) Teachers design a leaderboard which is updated periodically; 4) The teacher designs badges for the acquisition and progress of learning; 5) The teacher provides an understanding of competition and collaboration value; 6) The teacher appreciates all the efforts that have been made by students. This study is very useful as a guide for implementing gamification through productive struggle which was considered effective in the provision of education during the pandemic.